(untitled) (Journal of Hama University, 2024)
The cranial base plays a pivotal role in directing the craniofacial growth pattern; topographically and functionally, which in turn contributes to different growth patterns that may affect the location of the hyoid bone. In addition, it has been indicated that there may be an effect of race on the shape of the craniofacial structures and the face shape in the vertical direction. Therefore, the objective of this study was to describe the cranial base and the hyoid bone in Syrian adults with class II Division1 malocclusion with different Patterns of Vertical Growth using CBCT. The sample included 30 adults with Class II Division 1(11 males - 19 females). They are divided into 3 groups according to the sum of Bjork angles (Horizontal, Normal, Vertical growth pattern). A CBCT image was taken for each patient and the linear and angular measurements were performed using CS 3d imaging software. The results were analyzed using the Kruskal-Wallis test to compare between vertical facial groups and find out the significance of differences at significance level (P<0.05). The results showed that the angles of the cranial base were similar between the vertical facial groups in Class II Division 1, while the anterior and total cranial base were shorter in patients with vertical pattern compared to horizontal and normal groups. The upper incisors were similar between different vertical groups, while the lower incisors were more labial in horizontal growth group. As for the hyoid bone, there was no difference in its anterior-posterior and vertical position between vertical groups. However, the craniocervical angle has been smaller in patients with vertical growth pattern. The results provided further evidence that the craniofacial complex vary independently according to the population, the vertical facial pattern, and the sagittal classification.